Spiritual Intelligence as the Foundational Principle in the Conceptual Framework of Islamic Educational Psychology - Prasetio Rumondor (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic education aims to be holistic, not only developing intellectual abilities but also cultivating students’ moral, character, and spiritual dimensions. This study is important because current literature mostly focuses on measuring or applying spiritual intelligence, while few studies position it as a foundational principle of Islamic educational psychology. The study aims to develop a conceptual framework that places spiritual intelligence at the core of Islamic education and explores its implications for curriculum design, teaching strategies, and character development. The method employed is a conceptual literature review with descriptive-analytical analysis of relevant books, journals, and scientific publications. Findings indicate that integrating spiritual intelligence into curricula, humanistic approaches, and faith-based learning methods enhances ethical awareness, self-regulation, interpersonal competence, and holistic character development. In conclusion, spiritual intelligence should serve as a conceptual foundation in Islamic education. The study recommends designing curricula and teaching strategies that comprehensively emphasize moral-spiritual values.